The mitochondrial genome of Nemalecium lighti (Hydrozoa, Leptothecata). Issue 11 (2nd November 2021) - Macher, Jan-Niklas; Kayal, Ehsan; Duijm, Elza; van der Hoorn, Berry; Montano, Simone; Speksnijder, Arjen
Abstract: The hydrozoan species Nemalecium lighti (Hargitt, 1924) is widely distributed in tropical marine waters around the world. Here we report the complete linear mitochondrial genome of N. lighti from Sint Eustatius (Lesser Antilles). The mitochondrial genome with a length of 14, 320 bp encodes for 13 protein-coding genes, two tRNA genes, and two rRNA genes. Gene arrangement differs from that found in other species of the same taxonomic order and a phylogenetic analysis shows that based on mitochondrial genes, N. lighti clusters outside of the Leptothecata, rendering the order paraphyletic.